Supercritical CO2 technology: the next standard sterilization technique? - Soares, Gonçalo C. (2019)
Sterilization of implantable medical devices is of most importance to avoid surgery related complications such as infection and rejection. Advances in biotechnology fields, such as tissue engineering, have led to the development of more sophisticated and complex biomedical devices that are often composed of natural biomaterials. This complexity poses a challenge to current sterilization techniques which frequently damage materials upon sterilization. The need for an effective alternative has driven research on supercritical carbon dioxide (scCO(2)) technology. This technology is characterized by using low temperatures and for being inert and non-toxic. The herein presented paper reviews the most relevant studies over the last 15 years which cover the use of scCO(2) for sterilization and in which effective terminal sterilization is reported. The major topics discussed here are: microorganisms effectively sterilized by scCO(2), inactivation mechanisms, operating parameters, materials sterilized by scCO(2) and major requirements for validation of such technique according to medical devices' standards.